Cognitive development of very preterm born children at 11 years of age - Nyman, Anna (fi=Turun yliopisto|en=University of Turku|, 2019)
Very preterm birth poses a risk to adverse neurodevelopment. Specific cognitive impairments can be assessed at five years of age. Milder cognitive impairments, however, may only grow into deficits at school age. This thesis is a part of the regional and multidisciplinary follow-up project PIPARI (PIeniPAinoisten RIskilasten käyttäytyminen ja toimintakyky imeväisiästä kouluikään). The thesis consists of three original studies that present data on 11-year-old very preterm born children (birth weight ≤1500g and/or <32 gestational weeks) born between 2001 and 2004. In Study I, the cognitive profile of the very preterm born children and the associated risk factors were evaluated. In Study II, the educational abilities and received support services of the very preterm born children were compared against the controls. In Study III, the executive functions of the very preterm born children at home and at school were compared against the controls and associated risk factors were evaluated. The main findings of the thesis were that the cognitive profile of the children born very preterm was within the average range but with results significantly lower than the mean test norms. General cognitive development at five years of age was highly correlated with general cognitive development at 11 years of age. Very preterm born children without severe cognitive impairment had age-appropriate academic and classroom performance at school, but they received significantly more support services than the controls. Compared to the controls, very preterm born children without severe cognitive impairment only had more problems in terms of their working memory at school. In this thesis, the most clinically significant risk factors for adverse cognitive development at 11 years of age were major pathologies observed with brain magnetic resonance imaging at term, low paternal education, surgical necrotizing enterocolitis and male gender. The findings suggest that children born very preterm meet everyday challenges at middle school age better than their cognitive profile would let us to expect. The most important goal in long-term follow-up of school age very preterm children is to evaluate their performance in everyday life and to provide knowledge about how preterm birth may affect learning and to provide detailed cognitive assessments with low threshold if problems emerge.

Pikkukeskosena syntyneiden lasten kognitiivinen kehitys 11-vuotiaana Pikkukeskosuuteen liittyy kehityksellisiä riskejä. Kapea-alaiset kognitiivisen kehityksen häiriöt voidaan tutkia viiden vuoden iässä. Lievemmät kognitiivisen kehityksen häiriöt saattavat kuitenkin tulla esille vasta kouluiässä. Tämä väitöskirja on osa alueellista ja moniammatillista PIPARI-projektia (PIeniPAinoisten RIskilasten käyttäytyminen ja toimintakyky imeväisiästä kouluikään). Väitöskirja koostuu kolmesta alkuperäistutkimuksesta, jotka kuvaavat vuosina 2001-2004 syntyneiden pikkukeskosten (syntymäpaino ≤1500g ja/tai <32 raskausviikkoa) suoriutumista 11-vuotiaana. Tutkimuksessa I arvioitiin pikkukeskosten kognitiivinen profiili ja siihen yhteydessä olevia riskitekijöitä. Tutkimuksessa II pikkukeskosten koulusuoriutumista ja heidän saamiaan tukitoimia verrattiin täysiaikaisina syntyneiden verrokkilasten suoriutumiseen ja tukitoimiin. Tutkimuksessa III pikkukeskosten toiminnanohjauksen taitoja kotona ja koulussa verrattiin verrokkilasten suoriutumiseen sekä arvioitiin yhteydessä olevia riskitekijöitä. Tämän väitöskirjan yhtenä päälöydöksenä oli, että pikkukeskosten kognitiivinen profiili on ikäryhmän normaalialueella, mutta tulokset ovat kuitenkin merkittävästi ikäryhmän keskitasoa heikompia. Yleinen kognitiivinen kehitys viisivuotiaana ennusti hyvin yleistä kognitiivista kehitystä 11-vuotiaana. Pikkukeskoset, joilla ei ollut vaikeaa kognitiivisen kehityksen häiriötä, suoriutuivat ikätasoisesti koulussa, mutta saivat verrokkiryhmää enemmän tukitoimia. Pikkukeskosilla, joilla ei ollut vaikeaa kognitiivisen kehityksen häiriötä, oli koulussa työmuistiongelmia verrokkiryhmää useammin. Tässä väitöskirjassa kliinisesti merkitsevimpiä riskitekijöitä heikolle kognitiiviselle kehitykselle olivat merkittävä aivovamma lasketun ajan magneettikuvauksessa, isän matala koulutustaso, leikkaushoitoa vaatinut keskosen vaikea suolisairaus ja poika sukupuoli. Tutkimustulosten mukaan pikkukeskosten suoriutuminen arkipäivän haasteista alakouluiässä on parempaa kuin heidän kognitiivinen profiilinsa antaisi odottaa. Tärkein tavoite kouluikäisten pikkukeskosten seurannassa on arvioida heidän suoriutumistaan päivittäisistä haasteista, tarjota lisätietoa keskosuuden vaikutuksista oppimiseen sekä tarjota yksityiskohtaisia kognitiivisia tutkimuksia matalalla kynnyksellä, mikäli ongelmia ilmenee